Assessment of the ability of poly(l‐lysine)–poly(ethylene glycol) (PLL–PEG) hydrogels to support the growth of U87‐MG and F98 glioma tumor cells. Issue 21 (7th February 2018) - Gontran, Emilie; Juchaux, Marjorie; Deroulers, Christophe; Kruglik, Sergei; Huang, Nicolas; Badoual, Mathilde; Seksek, Olivier
ABSTRACT: Biomaterials that provide 3D‐like in vitro cell survival and proliferation are increasingly used to mimic the extracellular microenvironment in the context of a better understanding of tumorigenesis. In this study, a simple, affordable and fast technique to fabricate hydrogel matrices composed of poly(ethylene glycol) (PEG) and poly(l ‐lysine) (PLL) (as cell‐adhesive factor) were used to provide in vitro glioma cell growth. After UV photopolymerization of a precursor solution containing PEG‐diacrylate and easily obtainable PLL‐acrylate derivatives, F98 and U87‐MG cells (rat and human glioblastoma cell lines, respectively) were grown on top of different substrates that consist of combinations of PEG/PLL hydrogels and spontaneously formed cell aggregates of homogeneous sizes. Depending on the cell type, PEG and PLL concentrations, the cell aggregates patterns were different. The optimal combination to obtain cell survival and proliferation for both cell lines was determined as 3% PEG (w/v) and 0.001% PLL (w/v). This technique was also used to assess the efficacy of temozolomide and should be adaptable to other cancer cell lines to follow pseudo‐tumor growth in vitro . © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46287. Abstract :